Attitude Survey on Current Governance System at Tarakeshwar and Tokhain Kathmandu - Dr. Hari Prasad Adhikari, (Journal of Balkumari College, 2022)
This study aims to examinecomponents of local government's development for improving local governance in Nepal. Descriptive and analytical research design was used in this study. The data collected through a questionnaire from 150 respondents were used for analysis. The component of local government for improving local governance in Nepal was found satisfactory, but its implementation was found poor.The findings from this study provide information about Federalismpolicy in Nepal. It could be helpful to provide some particular guidelines to the policymakers for improving local governance. It suggests that appropriate policy must be adopted, and proper communication and information system should be developed.